The Impact of the 2019 El Nino on Soil Moisture in Nong Khuay village, Xieng Nguen district, Luangprabang province: Effects of Ground Cover - Lau, Yingshan; Daovongdeuan, Siphanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
Soil moisture is essential for agriculture, and is retained to different degrees through different soil management practices. This study describes the effects of ground cover on soil moisture at different sites - a vegetable garden, a regenerating bush fallow, a swidden rice field, a dry paddy rice field and a forest - in an upland village in Xieng Nguen district, Luangprabang province. Soil samples up to 1m deep were collected from each site over a 3-month period from end-November 2019 to end-February 2020. They were analysed for soil moisture, pH and soil texture using, respectively, the gravimetric method, a pH meter and the manipulative test. Our findings suggest that, while the presence of ground cover helps to reduce the loss of soil moisture, the ground cover’s thickness and density should be considered. Shade, soil texture and subsurface hydrology could also affect soil moisture. The impact of the 2019 weak El Nino was such that four of the five sites experienced at least a 0.1 decrease in soil moisture over the study period.